The Implementation of The Employee Leaving Input System of PT. Prima Sejati Sejahterah Boyolali - Risma Nur Hanifah; Nendy Akbar Rozaq Rais (Institut Teknologi Bisnis AAS Indonesia, 2021)
PT. PAN BROTHER is a multinational company that produces textiles headquartered in Jakarta, Indonesia. This company was founded in 1969. This company produces various kinds of clothing. Currently, PT. PAN BOTEHR, especially the branch in Boyolali, namely PT. Prima Sejati Sejahtera has conducted attendance by using a finger print machine and a computerized scanner. Employees who wish to take annual leave, maternity leave, official permits, and sick leave are already using a web-based system, by means of employees inputting attendance on a computer provided by the company. However, there are still employees who lack knowledge of science and technology and are still an obstacle to implementing the web-based system. This system can actually be accessed using a smart phone, so that employees do not need to ask attendance staff for help when inputting leave. And to recap the attendance report of HRD employees must also look for employee leave documents that are still in paper files, so that this can slow down the withdrawal of reports on a monthly basis. With this problem, the Company made an innovation by creating an online-based web application for inputting employee leave and the author also conducted research on the application of this web-based system using literature study and field studies in field objects. It is hoped that with this research, the system can be used by all employees to be more effective in inputting absences due to leave and can help alleviate the performance of HRD staff to be more flexible and efficient and reduce absenteeism reporting errors due to employee leave.